Delayed Treatment of Capsaicin Produces Partial Motor Recovery by Enhancing Dopamine Function in MPP + -lesioned Rats via Ciliary Neurotrophic Factor - Kim, Kyoung In; Baek, Jeong Yeob; Jeong, Jae Yeong; Nam, Jin Han; Park, Eun Su; Bok, Eugene; Shin, Won-Ho; Chung, Young Cheul; Jin, Byung Kwan (Experimental neurobiology, 2019)
Transient receptor potential vanilloid subtype 1 (TRPV1) on astrocytes prevents ongoing degeneration of nigrostriatal dopamine (DA) neurons in MPP -lesioned rats via ciliary neurotrophic factor (CNTF). The present study determined whether such a beneficial effect of astrocytic TRPV1 could be achieved after completion of injury of DA neurons, rather than ongoing injury, which seems more relevant to therapeutics. To test this, the MPP -lesioned rat model utilized here exhibited approximately 70~80% degeneration of nigrostriatal DA neurons that was completed at 2 weeks post medial forebrain bundle injection of MPP . TRPV1 agonist, capsaicin (CAP), was intraperitoneally administered. CNTF receptor alpha neutralizing antibody (CNTFRαNAb) was nigral injected to evaluate the role of CNTF endogenously produced by astrocyte through TRPV1 activation on DA neurons. Delayed treatment of CAP produced a significant reduction in amphetamine-induced rotational asymmetry. Accompanying this behavioral recovery, CAP treatment increased CNTF levels and tyrosine hydroxylase (TH) activity in the substantia nigra pars compacta (SNpc), and levels of DA and its metabolites in the striatum compared to controls. Interestingly, behavioral recovery and increases in biochemical indices were not reflected in trophic changes of the DA system. Instead, behavioral recovery was temporal and dependent on the continuous presence of CAP treatment. The results suggest that delayed treatment of CAP increases nigral TH enzyme activity and striatal levels of DA and its metabolites by CNTF endogenously derived from CAP-activated astrocytes through TRPV1, leading to functional recovery. Consequently, these findings may be useful in the treatment of DA imbalances associated with Parkinson's disease.